FORMATION OF STUDENTS' RELIGIOUS CHARACTER THROUGH THE EXAMPLE OF PAI TEACHERS AT MAN 1 PAMEKASAN - Erin Dwi Yuniawati; Cyntia Ela Maghfira; Riyadhotis Sholihah; Siti Juwairiyah; Abd. Mukhid; Anifah Khairah Ummah (Jurnal Asy-Syukriyyah, 2026)
This study aims to describe how Islamic Religious Education (PAI) teachers at MAN 1 Pamekasan implement their professional ethics and employ exemplary methods to foster religious character among students. This study employs a qualitative method, gathering data through observation, interviews, and document review. Primary data were obtained directly from teachers and students, whereas secondary data were sourced from pertinent documents and literature. The results indicate that PAI teachers at MAN 1 Pamekasan embody professional ethics through behaviors such as honesty, accountability, empathy, and attentiveness to students, all rooted in Quranic principles. Teachers implement the role-modeling approach by exemplifying good conduct in classroom instruction and everyday religious practices, including group prayers, Quran reading sessions, and fostering school-wide religious routines. Obstacles encountered encompass inconsistent teacher behaviors, limited student engagement, off-campus external factors, insufficient parental participation, excessive focus on cognitive learning, and adverse effects of technology. Thus, the ongoing practice of professional ethics via exemplary modeling by PAI teachers is essential for cultivating students' religious character.